Pemberdayaan Sosial Ekonomi Kelompok Wanita Tani Sejahtera melalui Wirausaha Kreatif Kaktus dan Sukulen di Desa Kabba, Kabupaten Pangkep - Sadriani, Andi; GH, Muliana; Hamka, Rezky Amalia; Pratama, Muh. Isbar (SMART: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Sejahtera Women's Farmers Group (KWT) in Kabba Village faces limitations in economic aspects, particularly in utilizing local entrepreneurship potential. The group does not yet have a well-organized productive business activity, despite the significant potential for cultivating ornamental plants such as cactus and succulents. The goal of this empowerment program is to enhance the economic capacity of KWT members through training, mentoring, and the application of technology in developing creative entrepreneurship based on cactus and succulents, thus creating an independent, competitive, and sustainable women’s business group. The solutions offered in this community service project include several interventions. In the production sector, the partners will be provided with cactus and succulent cultivation training. In business management, a simple administrative system will be introduced, covering financial record-keeping, stock management, and business planning. In the marketing aspect, the partners will be taught packaging techniques and digital marketing strategies through social media and digital platforms.